Classificação arquivística nos contextos dos arquivos universitários: uma análise de planos de classificação - PINHEIRO, Thais Aires (2017)
This study aimed to analyze the applicability of archival classification in agreement with the reality in the context of the university archives, as well as to carry out a comparative analysis between the classification plan of the USP and the classification codes of the CONARQ intermediate and final activities, highlighting their similarities and differences, and verifying whether it serves the purposes of organization, access, understanding and retrieval of information. To do so, the bibliographical research, was used as data collection method for the content of the classification in the university scope. From the analysis it was possible to perceive the importance of the correct classification of the archives, demonstrating the challenges for standardization of classification rules. Finally, through the study, it was possible to analyze the possibility of an optimization of information management, facilitating access to the user and thus allowing greater efficiency of classification.